Motivasi Sedekah Dalam Al-Qur’an: Studi Penafsiran Ayat-Ayat Sedekah Dalam Tafsir Al-Qur’anul Majid An-Nuur - Nadham Kharismawan, Kevin; Sulthoni, Akhmad; Murdianto (Kuras Institute, 2024)
This study examines the motivation for charitable giving (sadaqah) in asbi ash-Shiddieqy's Al-Qur’anul Majid through the lens of Bourdieu's theory. The significance of this research lies in integrating social theory with Qur'anic interpretation to explore how capital, habitus, and practice influence charitable actions. The methodology involves a qualitative analysis of ash-Shiddieqy's tafsir using Bourdieu's theory, while identifying gaps in previous studies related to the roles of symbolic and cultural capital and gender equality in charitable giving. The novelty of this research is its application of Bourdieu’s theory to investigate how metaphors in the tafsir and gender equality impact motivation and practice in charitable giving. The findings indicate that the metaphors in Al-Qur’anul Majid simplify the concept of sadaqah, making it easier to understand and implement, thereby increasing motivation. Gender equality in charitable giving, as outlined in ash-Shiddieqy's tafsir, promotes active participation from all genders and reinforces egalitarian values in charitable practices. Furthermore, mutual reminders within the community, according to the tafsir, play a crucial role in maintaining the quality and consistency of charitable actions, strengthening social capital, and shaping a habitus that supports sustainable giving. This study contributes significant insights by linking Qur'anic exegesis with contemporary social theory, offering new perspectives on how social and symbolic factors influence charitable practices within religious and social contexts.